2014
DOI: 10.1158/2159-8290.cd-14-0001
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Xenograft Models: An Emerging Platform for Translational Cancer Research

Abstract: Recently, there has been an increasing interest in the development and characterization of patient-derived tumor xenograft (PDX) models for cancer research. PDX models mostly retain the principal histologic and genetic characteristics of their donor tumor and remain stable across passages. These models have been shown to be predictive of clinical outcomes and are being used for preclinical drug evaluation, biomarker identification, biologic studies, and personalized medicine strategies. This article summarizes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
1,352
4
17

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,425 publications
(1,445 citation statements)
references
References 76 publications
20
1,352
4
17
Order By: Relevance
“…S5). Unlike immortalized cell lines, these patient-derived GBM cells can better preserve tumor phenotype and predict clinically relevant outcomes (26). Our data showed that patientderived GBM cells formed microsatellites surrounding main tumor in vivo (Fig.…”
Section: Trail Induces Apoptosis In Glioma Cells But Not In Hadscs Andmentioning
confidence: 70%
See 1 more Smart Citation
“…S5). Unlike immortalized cell lines, these patient-derived GBM cells can better preserve tumor phenotype and predict clinically relevant outcomes (26). Our data showed that patientderived GBM cells formed microsatellites surrounding main tumor in vivo (Fig.…”
Section: Trail Induces Apoptosis In Glioma Cells But Not In Hadscs Andmentioning
confidence: 70%
“…Third, membrane-bound TRAIL was chosen as a therapeutic agent overexpressed by polymeric nanoparticles, which markedly augment receptor clustering and apoptosis stimulation in cancer cells (30,31). Last, patient-derived GBM xenograft cells were used rather than immortalized cell lines, which have been shown to better at preserving tumor phenotype and predicting clinically relevant outcomes (26).…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of evidence, including high fidelity in mutational status, transcriptome, histology, polymorphism and copy number variation, also supports the notion that PDTX models remarkably resemble the pathophysiology of human tumors more closely than traditional Cancer-derived xenograft (CDX) models [16]. This convincing data suggests PDTX are informative models to study clonal evolution along serial passages, at the rates reported in primary tumors [17][18][19][20][21][22][23][24]. Notably, PDTX grow within a rich host environment and the relationship between human tumors and mouse host elements have been proven to be critical for the successful engraftment, growth and response to therapy [25].…”
Section: Introductionmentioning
confidence: 66%
“…On the contrary, cell lines, even when propagated in vivo, are derived from cancer cells that have adapted to growth outside a natural tumor microenvironment, resulting in genetic changes that are distinct from the genetic stress imposed on tumors in patients (44). Notwithstanding some limitations due to the drift of stromal components from human to mouse, PDXs represent a great challenge for oncology drug development, if viewed as complementary to other preclinical models (45). In this study, we have demonstrated that PDXs showed fidelity to the original tumor, as they maintain the morphologic features of a poorly differentiated colon adenocarcinoma and conserved the same KRAS mutation in the region of exon 2 of codon 12, observed in tumor of patient.…”
Section: Discussionmentioning
confidence: 99%